Teaching Romans backwards: a study guide to Reading Romans backwards by Scot McKnight - Castle Miller, Becky (1845 Books, an imprint of Baylor University Press, 2019)
Romans is perhaps the most read book of the New Testament and yet perhaps also the most misunderstood. Scot McKnight's Reading Romans Backwards turns our understanding around. Seeing Romans in a new way changes our view of ourselves and, in doing so, our grasp of the role of others in the church. Teaching Romans Backwards is a study guide and workbook to help readers engage McKnight's commentary. It breaks down the book into 15 lessons, each offering : the reading assignments with the pages of McKnight's book and the passages from Romans to read before class, a main point to focus the lesson, chapter summaries that draw out the learning highlights, classroom discussion questions, group learning activities to make the experience multidimensional, resources for further information that include websites, images, videos, and further reading, personal study questions to aid reflection on the text, a quiz, and further Bible study suggestions beyond Romans. The study guide is ideal for university classrooms, Sunday school classes, small group Bible studies, and even personal study. This companion guide will help you get the most out of Romans as you read or teach it backwards.